Metaphors in the narrative of Ephesians 2:11-22 motion towards maximal proximity and higher status - Jiménez, Oscar E. (Boston BRILL, 2022)
Intro -- Contents -- Acknowledgements -- List of Tables and Figures -- Abbreviations -- 1 Prologue -- 1 Previous Non-Metaphorical Approaches to Ephesians 2 -- 2 Previous Metaphorical Approaches to Ephesians 2 -- 3 The Scope of This Book -- 4 Overview of This Book -- 4.1 Stage Directions -- 4.2 The Drama -- 2 Stage Directions: Methodology for Framing Narrative -- 1 Introduction to Stage Directions -- 2 Unit 1: The Interaction of Narrative with Story, Epistle, and Metaphor -- 2.1 Narrative and Story -- 2.2 Narrative and Epistolary Literature -- 2.3 Narrative and Metaphor -- 3 Unit 2: Framing Metaphor and Metonymy -- 3.1 Frame Semantics -- 3.2 Conceptual Metaphors -- 3.3 Conceptual Metonymy -- 4 Conclusion to Stage Directions -- 3 Drama-Act I: From Outsiders to Insiders -- 1 Introduction to Act I -- 1.1 Overview of the Drama -- 1.2 Overview of Act I: Transformation: "Then" and "Now" -- 2 Act I, Scene 1: Then - "Remember Who You Were" -- 2.1 Literary Background -- 2.2 Ephesians 2:11 - Remember -- 3 Act I, Scene 2: Now - "Let Me Tell You Where You Are Now" -- 3.1 Ephesians 2:13 -- 4 Conclusion to Act I -- 4 Drama-Act II: One Plus One Equals One -- 1 Introduction to Act II -- 1.1 Overview of the Drama -- 1.2 Overview of Act II: Explanation - "Why" and "How" -- 2 Act II, Scene 1: What Christ Did -- 2.1 Christ Is Peace -- 2.2 Christ Makes Peace -- 3 Act II, Scene 2: What Christ Enables the Audience to Experience -- 3.1 Christ Preaches Peace -- 3.2 Christ Enables Peace (with the Father) -- 4 Conclusion to Act II -- 5 Drama-Act III: A More Perfect Union -- 1 Introduction to Act III -- 1.1 Overview of the Drama -- 1.2 Overview of Act III: The Result "So Then" -- 2 Act III, Scene 1: A Shared Identity -- 2.1 The Outside -- 2.2 The Inside -- 2.3 god's territory is a city -- 2.4 god's territory is a household -- 3 Act III, Scene 2: A Shared Purpose.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books; Hochschulschrift